Multilateration and triangulation algorithms for localization of wireless sensor nodes - Sahil Gupta. (2009)
In this final year project, the author discusses the various methods of Localization techniques like Trilateration and Multilateration using Wireless Sensor Nodes. A Wireless Sensor Network (WSN) consists of a number of sensors spread across a geographic area. Each sensor node has wireless communication capability and some level of intelligence for signal-processing and networking of data.